Food and housing insecurity and health status among U.S. adults with and without prior military service - Marc B. Schure; Jodie G. Katon; Edwin Wong; Chuan-Fen Liu (Elsevier, 2016)
Food and housing insecurity may contribute to poorer mental and physical health. It is unclear as to whether those with prior military service, compared to those without, are more vulnerable to these current stressors. The objective of this study was to use U.S. population-based data to determine whether prior military service moderates the association of food and housing insecurity with poor mental and physical health.We analyzed data from nine states administering the Social Context module from the 2011 and 2012 Behavioral Risk Factor Surveillance System. Multivariable logistic regression was used to examine the associations of housing and food insecurity with poor mental and physical health and potential modification by military service. Compared with those with a history of military service, those without had higher prevalence of food insecurity (23.1% versus 13.7%) and housing insecurity (36.0% versus 22.5%). Food insecurity was associated with poor mental and physical health (mental health: odds ratio (OR)=3.47, 95% confidence interval (CI)=[3.18-3.77]; physical health: OR=3.21, 95% CI=[2.92-3.53]). Similar associations were observed between housing insecurity and poor mental and physical health. Prior military service was significantly associated with poor physical health. Interaction terms of prior military service with food and housing were not statistically significant. Food and housing insecurity does not appear to differentially impact mental and physical health among those with and without military service. Keywords: Food and housing insecurity, Mental and physical health, Military service